Organizational Support and Inclusive Leadership Boost Employee Innovation Through Work Motivation - Asih Niati; Asah Wiari; Erlina Dewi Endah Amaliyah; Mohamad Sodikin (Universitas Mercu Buana, 2026)
Objectives: The existence of various problems related to innovative performance among employees and numerous controversies in previous studies became the background of this study. The gap that exists between survey and reality as well as inconsistencies from previous studies need further review. Therefore, the aim of this study is to provide findings and recommendations to solve the phenomena related to innovative performance.Methodology: The data collection was carried out using a questionnaire distributed via Google Form to respondents who meet the determined criteria. Structural Equation Modeling (SEM) was used to analyze the data.Finding: The results show that Perceived Organizational Support and Inclusive Leadership have a positive and significant effect on Work Motivation, partially. It also shows that Perceived Organizational Support, Inclusive Leadership and Work Motivation have a positive and significant effect on Employee Innovative Performance. However, Work Motivation failed to become a mediating variable between Perceived Organizational Support on Employee Innovative Performance. On the other hand, Work Motivation is successful in becoming a mediating variable for Inclusive Leadership on Employee Innovative Performance.Conclusions: Organizations should adopt HR development policies that promote open communication and coaching, which address employees’ need for support from leaders aligned with training initiatives and provide a platform for dialogue. With a millennial workforce, inclusive leadership is critical, as employees look for leaders who encourage change and creative thinking.